Draft Genome Sequence of Fusarium fujikuroi B14, the Causal Agent of the Bakanae Disease of Rice - Jeong, Haeyoung (American Society for Microbiology, 2013)
Here, we present the genome sequence of a Korean strain (B14) of Fusarium fujikuroi, a fungal rice pathogen. The final assembly consists of 455 contigs with 43,810,516 bp and 14,017 predicted genes. Comparison with the F. verticillioides 7600 genome revealed a reference coverage of 83% (66.3% of reads mapped).